Quantitative Identification of Detrital Minerals by Mineral Characteristic Automatic Analysis System and Error Analysis with Traditional Microscopic Identification - Ze NING; Lei XU; Xuehui LIN; Yuanyuan ZHANG; Yong ZHANG (Yankuang ceshi)
The analysis of detrital minerals is widely used in the study of sediment sources and material diffusion, and is of great significance in analyzing sedimentary dynamic environment and oceanic dynamic characteristics. However, for a long time, the acquisition of detrital mineral data has relied mainly on optical microscopes as tools and manual identification, which is labor-intensive and inefficient. In order to obtain scientific and effective mineral identification data in a timely fashion, a thermal field emission scanning electron microscopy with energy dispersive spectroscopy attached and an automated mineral identification and characterization system (AMICS) were used. For the first sample, 25 mineral species were identified by the AMICS system and 25 mineral species were identified by artificial identification with stereomicroscope and polarizing microscope. For the second sample, 26 mineral species were identified by the AMICS system, and 27 mineral species were identified by artificial identification. The two methods identified similar types of detrital minerals, and the absolute error of each mineral content was less than 5%. The AMICS system can be used to identify oxides (limonite, chromite, etc.), phosphates (apatite, etc.), sulfates (barite, etc.), sulfides (pyrite, etc.), carbonates (calcite, dolomite, etc.), and some silicates (zircon, titanite, olivine, quartz, potassium feldspar, sodium feldspar, garnet group, etc.) accurately but it is difficult to accurately identify polymorphic and isomorphic detrital minerals based solely on mineral chemical composition. The problem of layered silicate minerals easily falling off layer by layer during sample preparation needs to be solved.